Síntese e avaliação farmacológica de novos híbridos moleculares 3-O-peperidinil-N-benzil-acilidrazônicos, planejados como candidatos a fármacos simbióticos: antiocolinesterásicos e anti-inflamatórios - Rocha, Miguel Divino Da (2010)
The increasing in life quality expectancy observed in recent decades, has focused great attention over diseases associated with longevity, like Alzheimer's disease (AD) that represent great scientific challenges to science and public health programs. In Brazil, it is estimated that 1.2 million people are suffering from AD, a chronic, progressive, and incurable disease until now. This pathology is characterized by progressive loss in memory and cognitive abilities, with death of cholinergic neurons in many areas of the CNS, accompanying by a dramatic reduction in release of neurotransmitters, particularly acetylcholine, the most important of them associated to AD’s physiopathology. In addition, numerous studies have pointed an important contribution of neuro-inflammatory process in the advance of neurodegeneration and neuronal loss. Nowadays there are only four drugs commercially available for AD treatment and the search for new chemical entities capable to diminish or blockade the progress of AD is still a great challenge to medicinal chemists. As a part of an ongoing research program, we decide to investigate the design of a new series of acetylcholinesterase (AChE) inhibitors that could also exert anti-inflammatory properties, by an innovative dual or symbiotic pharmacological profile. So, a novel structural pattern was drawn by molecular hybridization of two commercial acetyl cholinesterase inhibitors, rivastigmine and donepezil, including an acylhydrazone subunit, that was expected to introduce anti-inflammatory properties. The synthetic route of the new series of hybrid compounds (29) was planned from 4-carboxy-benzaldehyde (30), as a starting material, which resulted in 21 new molecules, differing in the substituent at C-3 position of the piperidine ring and at the benzylic subunit connected to the acylhydrazone spacer of the basic skeleton 29. Pharmacological evaluation of these series showed significant anti-inflammatory properties of compounds LFQM-54, LFQM-55, LFQM-65, LFQM-67 and LFQM-69, among which LFQM-67, LFQM-69 and LFQM-65 were the most active. The in vitro evaluation of inhibitory activity of acetylcholinesterase disclosed that acylhydrazones derivatives with a hydroxyl group in the piperidine subunit showed the higher inhibitory activity AChE, ranging 65-91%, with IC50 ranging from 3.02 to 30.54 μM. Among these, LFQM-57 was the most potent, and LFQM-67 was also one of the compounds with higher anti-inflammatory potency and the second most potent in AChE inhibition, followed by LFQM-55. Moreover, LFQM-69, with an ethylcarbamoyl substituent at the piperidine moiety, was extremely powerful in the inflammatory model, without significative anti-cholinesterase activity. These findings suggest that the piperidine subunit with a free hydroxyl group at position C-3 is an essential pharmacophoric group for dual anti- inflammatory and acetylcholinesterase inhibitory profile. Moreover, compounds LFQM-74, LFQM-75 and LFQM--88, which showed potent inhibitors of AChE, were not still evaluated in inflammatory models and may additional contribute to the identification of other innovative drug prototype candidates.